PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS PROJECT BASED LEARNING (PJBL) BERBANTU MEDIA OASIS DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) DI MADRASAH IBTIDAIYAH - Siti Nurjanah; Pina Indah Sayekti; Wahyu Warastuti; Vitri Astuti; Anatri Desstya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of Contextual Teaching and Learning (CTL) based on Project Based Learning (PjBL) with interactive digital media OASIS "Ayo Belajar Metamorfosis" in learning Natural and Social Sciences (IPAS) on metamorphosis material in grade III of Madrasah Ibtidaiyah. Using a qualitative approach with a case study design, data were obtained through observation, interviews, and documentation, involving 28 students at MI Muhammadiyah Karanganyar. The results of the study indicate that the Contextual Teaching and Learning Approach based on Project Based Learning assisted by OASIS media "Ayo Belajar Metamorfosis" can be applied effectively in learning Natural and Social Sciences (IPAS) in grade III of Madrasah Ibtidaiyah. OASIS features such as learning objectives, materials, videos, quizzes, and assessments, ice breaking, wisdom combined with animal life cycle observation projects can help students understand concepts in depth, develop collaboration skills, critical thinking, and creativity. The use of interactive media makes learning more interesting, relevant, and enjoyable.